Electrophoretic Pattern of Hereditary Haemoglobin Disorders in Bangladesh (Journal of Dhaka Medical College, 2010)
Background: Genetic defects of haemoglobin are the most common genetic disorders and affect around 7% of world Population, occur in tropical and sub tropical areas. â thalassaemia is more common in the Mediterranian region while á thalassaemia is more common in the Far East. Objective: To Find out the pattern of haemoglobin disorders and to evaluate and compare the diseases in study population. Methods: A total number of 210 subjects with age ranged from 2 to 72 years of both sexes were included in the study. The present study was conducted in out patient department (OPD) of Haematology, Bangabandhu Sheikh Mujib Medical University (BSMMU,) Dhaka. Bangladesh. During the period of January 2007 to December 2007, patients were selected on the basis of morphological blood film examination and Hb- electrophoresis on cellulose acetate at PH 8.6. Results: Among the 210 Subjects, thalassaemia trait were (47.14%), HbE-beta thalassaemia were 30.47%, HbE Trait 13.3%, HbE disease (5.71%) and thalassaemia major were (3.33%). Conclusion: It is evident that, Hereditary Haemoglobin disorders are quite common in Bangladesh and this disorders are inherited as autosomal recessive Mendelian pattern affecting both male and female. Key words: Electrophoretic pattern; Haemoglobin disorders. DOI: 10.3329/jdmc.v19i1.6250 J Dhaka Med. Coll. 2010; 19(1) : 39-42.